2022
DOI: 10.1111/ene.15555
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sjögren syndrome‐related peripheral neuropathy: A systematic review and meta‐analysis

Abstract: This is a repository copy of Primary Sjögren syndrome-related peripheral neuropathy: a systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 72 publications
(301 reference statements)
0
10
0
2
Order By: Relevance
“…Gemignani et al suggested increasing age as a risk factor for the development of polyneuropathy in pSS patients [ 14 ]. Liampas et al also observed increasing age as one of risk factors for developing PN [ 15 ]. A possible explanation is microangiopathic changes in the endoneurial vessels [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gemignani et al suggested increasing age as a risk factor for the development of polyneuropathy in pSS patients [ 14 ]. Liampas et al also observed increasing age as one of risk factors for developing PN [ 15 ]. A possible explanation is microangiopathic changes in the endoneurial vessels [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recently published EULAR recommendations suggest first-line immunosuppressive therapy in patients with axonal sensory polyneuropathy [ 24 ]. Glucocorticoids are the most commonly used treatment option of managing pSS-related PN, when associated with vasculitis, followed by the use of IVIG [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sjogren's syndrome (SS) is a high-rate, common, and harmful global disease with higher potential morbidity and is an essential menopausal and aging disease [34][35][36]. The disease is characterized by xerostomia with dysfunction of salivary gland secretion as the initiating factor, which affects the whole body's health [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…This caused a great quantity of proin ammatory lymphocyte in ltration, when the SG tissue chemokines of NOD mice increased signi cantly, such as Th17 cells in ltrating into SG tissue, and the in ltrating pro-in ammatory lymphocytes will secrete pro-in ammatory cytokines to form a vicious circle, leading to the permanence of autoimmunity. Massive lymphocyte in ltration leads to decreased secretion of the affected gland [35,36]. We found that the increase of CD4 + GRK2, Th17 + CXCR3 in mice spleen promoted lymphocyte in ltration into SG tissue, and a large number of Th17 cells appear in SG tissues and peripheral tissues of mice, Treg cells are reduced, and the proportion of Th17/Treg cells is out of balance, it promotes the progression of pSS.…”
Section: Discusstionmentioning
confidence: 94%